Neocosmospora rubicola, a stem rot disease in potato: Characterization, distribution and management - Riaz, Muhammad; Akhtar, Naureen; Msimbira, Levini A.; Antar, Mohammed; Ashraf, Shoaib; Khan, Salik Nawaz; Smith, Donald L. (Frontiers in Microbiology, 2022)
Potato (Solanum tuberosum L.) is one of the most important crops in maintaining global food security. Plant stand and yield are affected by production technology, climate, soil type, and factors such as insect and disease attack prevalence. Numerous fungal diseases are known to negatively affect performance and quality of potato. Stem rot disease caused by fungi is most important in reduction of potato production. Neocosmospora rubicola, a fungal pathogen causing stem rot in potato causes stunted growth and yellowing of leaves with grayish-black stems as a typical symptom. The infectivity of N. rubicola across a number of crops indicates the need to search for appropriate management approaches. Synthetic pesticides application is a major method to mitigate almost all potato diseases at this time. However, these pesticides significantly contribute to environmental damage and continuous use leads to pesticide resistance by pathogens. Consumers interest in organic products have influenced agronomists to shift towards the use of biologicals in controlling most pathogens, including N. rubicola. This review is an initial effort to carefully examine current and alternative approaches to N. rubicola control that are both environmentally safe and ecologically sound. Therefore, this review aims to draw attention to the N. rubicola distribution and symptomatology, and sustainable management strategies for potato stem rot disease. It is shown that bacterial formulation (BF) with synthetic fertilizer has the potential to increase the tuber yield of potato in healthy soil as well as in the soil infested with N. rubicola. Phosphorus applications along with the BF can improve the working efficiency of the bacterial strains. However, nitrogen fertilizer can favor N. rubicola infestation without interfering with the working of the strains. To control N. rubicola infestation, with maximum tuber yield benefits, a pre-application of the biofertilizer is shown as a better option, based on the current literature.